Critical care assessment handbook - Murray, Sharron E. 4 0 16; DrPH. White, Barbara S.; 5 (Philadelphia : W.B. Saunders, 1999)
This portable, practical handbook provides the comprehensive knowledge base you need to thoroughly and accurately assess critically ill patients - both inside and outside of the ICU. It explains how, when, and why to use various assessment approaches based on each individual patient's situation.--BOOK JACKET.
I. Techniques and Types of Assessment. 1. Techniques of Assessment. 2. Types of Assessment. 3. The Critically III Geriatric Patient -- II. Focused Assessment: Techniques and System Disorders. 4. Respiratory Assessment. 5. Cardiovascular Assessment. 6. Neuromuscular Assessment. 7. Gastrointestinal Assessment. 8. Renal Assessment. 9. Endocrine Assessment. 10. Hematologic Assessment. 11. Immunologic Assessment. 12. Multisystem Disorders -- III. Common Laboratory Studies and Bedside Techniques. 13. Common Laboratory Studies. 14. Bedside Monitoring Techniques.
Includes bibliographical references (p. 745-754) and index.
Keywords: 2 -- 0; 6; methods -- Intensive care nursing;Nursing assessment;Critical Care;Nursing Assessment -- 20 -- Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks.;Handbooks.; 20; 2